Implementation of European Society of Gastrointestinal Endoscopy (ESGE) recommendations for small-bowel capsule endoscopy into clinical practice: Results of an official ESGE survey - Lazaridis, Lazaros-Dimitrios; Tziatzios, Georgios; Toth, Ervin; Beaumont, Hanneke; Dray, Xavier; Eliakim, Rami; Ellul, Pierre; Fernandez-Urien, Ignacio; Keuchel, Martin; Panter, Simon; Rondonotti, Emanuele; Rosa, Bruno; Spada, Cristiano; Jover, Rodrigo; Bhandari, Pradeep; Triantafyllou, Konstantinos; Koulaouzidis, Anastasios; on behalf of the ESGE Research Committee Small-Bowel Working Group (Endoscopy, 2021)
Background We aimed to document international practices in small-bowel capsule endoscopy (SBCE), measuring adherence to European Society of Gastrointestinal Endoscopy (ESGE) technical and clinical recommendations.Methods Participants reached through the ESGE contact list completed a 52-item web-based survey.Results 217 responded from 47 countries (176 and 41, respectively, from countries with or without a national society affiliated to ESGE). Of respondents, 45 % had undergone formal SBCE training. Among SBCE procedures, 91 % were performed with an ESGE recommended indication, obscure gastrointestinal bleeding (OGIB), iron-deficiency anemia (IDA), and suspected/established Crohn’s disease being the commonest and with higher rates of positive findings (49.4 %, 38.2 % and 53.5 %, respectively). A watchful waiting strategy after a negative SBCE for OGIB or IDA was preferred by 46.7 % and 70.3 %, respectively. SBCE was a second-line exam for evaluation of extent of new Crohn’s disease for 62.2 % of respondents. Endoscopists adhered to varying extents to ESGE technical recommendations regarding bowel preparation ( > 60 %), use in those with pacemaker holders (62.5 %), patency capsule use (51.2 %), and use of a validated scale for bowel preparation assessment (13.3 %). Of the respondents, 67 % read and interpreted the exams themselves and 84 % classified exams findings as relevant or irrelevant. Two thirds anticipated future increase in SBCE demand. Inability to obtain tissue (78.3 %) and high cost (68.1 %) were regarded as the main limitations, and implementation of artificial intelligence as the top development priority (56.2 %).Conclusions To some extent, endoscopists follow ESGE guidelines on using SBCE in clinical practice. However, variations in practice have been identified, whose implications require further evaluation.